2004
DOI: 10.1177/1534484304263335
|View full text |Cite
|
Sign up to set email alerts
|

Employee Burnout: A Meta-Analysis of the Relationship Between Age or Years of Experience

Abstract: This study examined the relationship between age or years of experience and employee burnout by performing a meta-analysis on research studies that present findings on relationships between employee burnout and age or years of experience. The problem has practical significance in that the appropriateness of approaches to addressing employee burnout may depend on whether age or years of experience is a factor related to burnout. Results indicated that there was a small negative correlation between employee age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
251
11
36

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 341 publications
(325 citation statements)
references
References 45 publications
27
251
11
36
Order By: Relevance
“…Yapılan bir meta analize göre, genç yaşta olanlar ve deneyimi az olan çalışanlar daha fazla tükenmektedirler (13). Çalışmamızda yaşlara göre tükenmişlik ölçeğinin 3 alt boyutu karşılaştırıldığında KB puanlarının 40 yaş ve üzeri hemşirelerde, 20-29 ve 30-39 yaş arası hemşirelere göre daha düşük olduğu saptandı.…”
Section: Discussionunclassified
“…Yapılan bir meta analize göre, genç yaşta olanlar ve deneyimi az olan çalışanlar daha fazla tükenmektedirler (13). Çalışmamızda yaşlara göre tükenmişlik ölçeğinin 3 alt boyutu karşılaştırıldığında KB puanlarının 40 yaş ve üzeri hemşirelerde, 20-29 ve 30-39 yaş arası hemşirelere göre daha düşük olduğu saptandı.…”
Section: Discussionunclassified
“…For instance, based on the study by Fisher (2011) in which 385 current and potential advanced secondary level teachers of Southeastern United States participated, the sense of burnout between novice and experienced teachers was significantly different, meaning that the new teachers showed higher levels of burnout. Additionally, the result of a meta-analysis, which concerned 20 unique samples of 18 studies in the field on 3941 samples, investigating any relationship between burnout and age or years of experience, indicated that there was a significant but small negative association between years of experience and burnout (Brewer & Shapard, 2004). These findings may be owing to the fact that teachers usually embark on such a demanding career with a great deal of enthusiasm, but after a short period of teaching they encounter variety of unexpected difficulties for which they are not able to find either a source or support.…”
Section: Discussionmentioning
confidence: 99%
“…Neminovno se nameće odgovor kojeg se veliki broj istraživača drži, da pored prirode posla, osobine ličnosti igraju važnu ulogu u razvijanju sindroma izgaranja (Bakker & Schaufeli, 2000;Brewer & Shapard, 2004;Colbert, Mount, Harter, Witt, & Barrick, 9 PROSVETNIH RADNIKA: ULOGA SITUACIONIH I INDIVIDUALNIH FAKTORA 2004; Ghorpade, Lackritz, & Singh, 2007;Hobfoll & Freedy, 1993;Maslach et al, 2001;McVicar, 2003;Mount, Johnson, Ilies, & Barrick, 2002;Zellars, Perrewe, & Hochwärter, 2000). Prema tim istraživanjima, ličnost u značajnoj meri može objasniti fenomen izgaranja.…”
Section: Uvodunclassified